Ilex rotunda Thunb Protects Against Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice by Restoring the Intestinal Mucosal Barrier and Modulating the Oncostatin M/Oncostatin M Receptor Pathway - Li, Yao; Yang, Xu; Yuan, Jia-ni; Lin, Rui; Tian, Yun-yuan; Li, Yu-xin; Zhang, Yan; Wang, Xu-fang; Xie, Yan-hua; Wang, Si-wang; Zheng, Xiao-hui (Frontiers in Pharmacology, 2022)
Ilex rotunda Thunb (IR) is a traditional Chinese medicine used for the clinical treatment of gastric ulcers and duodenal ulcers; however, the effect of IR on ulcerative colitis (UC) and its underlying mechanism remains unclear. This study investigated the therapeutic effect of IR on UC mice induced by dextran sulfate sodium (DSS) as well as the potential underlying mechanism. The main components of IR were analyzed by ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry. Then we established a model of UC mice by administering 2.0% DSS for 7 days followed by 2 weeks of tap water for three cycles and administered IR. On day 56, the disease activity index (DAI), colon length, pathological changes, and inflammatory response of the colon tissue of mice were assessed. The oxidative stress and apoptosis of colon tissue were detected, and the integrity of the intestinal mucosal barrier was evaluated to assess the effect of IR. Furthermore, the relationship between oncostatin M (OSM) and its receptor (OSMR) in addition to the IR treatment of UC were evaluated using a mouse model and Caco2 cell model. The results showed that IR significantly alleviated the symptoms of UC including rescuing the shortened colon length; reducing DAI scores, serum myeloperoxidase and lipopolysaccharide levels, pathological damage, inflammatory cell infiltration and mRNA levels of interleukin one beta, tumor necrosis factor alpha, and interleukin six in colon tissue; alleviating oxidative stress and apoptosis by decreasing kelch-like ECH-associated protein 1 expression and increasing nuclear factor-erythroid factor 2-related factor 2 and heme oxygenase-1 protein expression; and promoting the regeneration of epithelial cells. IR also promoted the restoration of the intestinal mucosal barrier and modulated the OSM/OSMR pathway to alleviate UC. It was found that IR exerted therapeutic effects on UC by restoring the intestinal mucosal barrier and regulating the OSM/OSMR pathway.